The right to the city: foreign legislative and enforcement practice - A. S. Kartashov (Правоприменение)
The subject. In the 20th century the problems of urbanization began to be discussed at the international level. In the early of the present century the international community moved to develop standards for human rights in cities. At the same time, special attention was given to the right to the city. The article is devoted to the analysis of foreign legislation and law enforcement of the right to the city. Examples of states in which the right to the city has been reflected in legislation, as well as states in which the right to the city has been recognized through judicial decisions, are discussed separately.Only a few studies can be found in Russian legal science, which fragmentarily analyzed the experience of foreign countries (primarily Brazil) in terms of the consolidation and recognition of the right to the city. Therefore, the purpose of the article is to summarize comparative legal approaches in interpreting the right to the city, as well as to identify differences in them.The methodology of the study includes general scientific methods of cognition (methods of analysis, system approach, deduction and induction), special methods of cognition (comparative-legal, formal-legal) and method of interdisciplinary research.The main results. The right to the city has been legislated in the states of South and Central America. This is explained by two reasons: the high level of urban population and false urbanization. Three states were chosen for the study: Ecuador, Brazil and Mexico. The right to the city has obtained the status of a constitutional right in Ecuador. In Brazil the foundations for the right to the city were laid at the constitutional level. However, it was set forth in a separate law – the City Statute of 2001. It is noted that the right has not become declarative. It has had a significant impact on urban planning regulation and the protection of the rights of citizens. The right to the city is considered as one of the principles of urban planning policy in Mexico and was established in Constitution of Mexico City.It is also analyzed the experience of states in which the right to the city has not been formalized. South Africa and India, where the right to the city has actually been recognized by the courts in resolving housing disputes, are selected as examples. This allowed the author to state that even in the absence of formalization, the idea of the right to the city can be used to protect the rights of citizens.the possibility of application of the right to the city in the states of Europe and North America, the author notes the widespread use of the other approach to the protection of the rights of the urban population – the concept of “human rights in the city”. However, the author provides arguments in favor of the right to the city and states that the foundations for its development in the states of Europe and North America are laid by the European Charter for the Safeguarding of Human Rights in the City.